RECALIBRATING THE RIGHT TO PRIVACY IN THE DIGITAL AGE: LEGAL CHALLENGES AND CONSTITUTIONAL SAFEGUARDS IN THE ERA OF TECHNOLOGICAL INTRUSION - Yadav, Rachna; Varshney, Dr. Rahul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The right to privacy started as a secondary constitutional matter before it elevated to basic status because of technological advancements. The constitution of India witnessed a major transformative moment following the decision made in Justice K.S. Puttaswamy v. Union of India . The 2017 Union of India (2017) decision legitimized privacy protections under the purview of Article 21. The digital age has introduced multiple sophisticated threats to privacy rights which cover both corporate information collection through AI systems and state-level surveillance and predictive law enforcement. The paper explores privacy law development while assessing protection mechanisms in the constitution and statutes alongside investigating fresh technology hurdles. The research uses GDPR standards together with the American sectoral model in a comparative analysis to show that existing legal norms require adjustment. The paper advocates for extensive regulatory structures together with ethical governance systems and court-based privacy protections because technological surveillance has become commonplace.